Resin composition, adhesive film and printed circuit board containing the same

By using the combination of the first toughening agent and the second toughening agent in the adhesive film, the problem of deterioration of the adhesive film caused by high-filled inorganic fillers is solved, and the integration of high Tg, low CTE and high copper foil peel strength is achieved. Performance, suitable for printed circuit boards with multi-layer laminated boards.

CN116218139BActive Publication Date: 2025-02-14GUANGDONG SHENGYI SCI TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211622418.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2025-02-14
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

After adding high-filled inorganic filler, the toughness of the existing adhesive films becomes poor, making it difficult to simultaneously improve the toughness and maintain a high glass transition temperature (Tg), a low coefficient of thermal expansion (CTE) and a high copper foil peel strength.

Method used

The resin composition using a combination of a first toughening agent (such as nitrile rubber, acrylic rubber or core-shell rubber) and a second toughening agent (polyarylethernitrile) can improve the toughness of the adhesive film while maintaining high Tg, low CTE and high copper foil peel strength.

Benefits of technology

It effectively solves the problem of deterioration of toughness caused by high-filled inorganic fillers, achieves higher Tg, copper foil peel strength and low CTE performance, excellent comprehensive performance, suitable for printed circuit boards with multi-layer laminated plates, especially Multi-layered laminated plates of thin lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004002613640000021
    Figure BDA0004002613640000021
  • Figure BDA0004002613640000111
    Figure BDA0004002613640000111
Patent Text Reader

Abstract

The present invention provides a resin composition and an adhesive film and a printed circuit board comprising the same, wherein the resin composition comprises the following components in parts by weight: 25-70 parts of resin, 30-60 parts of filler, 1-10 parts of a first toughening agent and 5-15 parts of a second toughening agent, wherein the first toughening agent comprises any one or a combination of at least two of nitrile rubber, acrylic rubber, core-shell rubber or phenolic resin, and the second toughening agent is polyarylether nitrile. In the present invention, two toughening agents are used in combination to exert a synergistic effect, so that the adhesive film and the resin-coated copper foil prepared by the resin composition can better solve the problem of toughness degradation caused by the addition of highly filled inorganic fillers, and at the same time have higher Tg, high copper foil peeling strength and low CTE performance, and can be applied to printed circuit boards of multilayer laminates, especially printed circuit boards of multilayer laminates for making fine circuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin adhesive films and relates to a resin composition and an adhesive film and a printed circuit board containing the same. Background Art

[0002] As electronic information products are mainly oriented towards the design trend of being light, thin, short and multifunctional in the future, the printed circuit substrate, as the main support for electronic components, is also constantly improving its technical level to provide high-density wiring, thin shape, fine aperture, multi-dimensional, etc. The substrate material determines the performance of the printed circuit substrate to a large extent, so it is urgent to develop a new generation of base materials.

[0003] Adhesive films or resin-coated copper foils without reinforcement materials are being developed and applied as a new generation of matrix materials because they can achieve thinner shapes, high-density wiring, fine pores, and multi-dimensional stereoscopic molding. Since there is no reinforcement material, high-filled inorganic fillers are generally added to improve the thermal expansion coefficient, chemical resistance, mechanical strength, etc. of the adhesive film material. However, it is precisely because of the introduction of high-filled inorganic fillers that the toughness of the adhesive film deteriorates. In order to compensate for the toughness, toughening agents such as rubber are usually added for toughening. However, the newly introduced toughening agents will deteriorate other properties. How to improve the toughness of the adhesive film without reducing other properties, such as Tg, CTE, modulus, etc., is the focus of research in this field.

[0004] Therefore, in the art, it is desired to develop a material for fine circuits that can improve the toughness of the film by adding a high-filler filler, and at the same time has a high Tg and a low CTE, a high copper foil peel strength and a relatively high modulus. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a resin composition, and an adhesive film and a printed circuit board containing the same.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides a resin composition, comprising the following components in parts by weight:

[0008]

[0009] The first toughening agent comprises any one of nitrile rubber, acrylic rubber, core-shell rubber or phenolic resin or a combination of at least two thereof;

[0010] The second toughening agent is poly(arylene ether nitrile).

[0011] In the present invention, the first toughening agent and the second toughening agent are used in combination to exert a synergistic effect, so that the adhesive film and the resin-coated copper foil prepared from the resin composition can better solve the problem of poor toughness caused by the addition of high-filled inorganic fillers, and at the same time have higher Tg, high copper foil peeling strength and low CTE performance, and have excellent comprehensive performance. They can be applied to printed circuit boards of multi-layer laminates, especially printed circuit boards of multi-layer laminates with fine circuits.

[0012] In the present invention, the content of resin in the resin composition is 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts, 60 parts, 65 parts, 68 parts or 70 parts.

[0013] In the present invention, the content of filler in the resin composition is 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts or 60 parts.

[0014] In the present invention, the content of the first toughening agent is 1 part, 2 parts, 3 parts, 5 parts, 7 parts or 10 parts.

[0015] In the present invention, the content of the second toughening agent is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0016] In the present invention, the poly(arylene ether nitrile) may be a commercially available product, including but not limited to: PEN-1100 of Sichuan Chemical New Materials, HC-G of Sichuan Feiya New Materials, or PEN ID300 of Idemitsu Kosan of Japan.

[0017] In the present invention, the "parts" and "parts by weight" involved are all calculated based on solid content and do not include solvents, dispersants, etc.

[0018] Preferably, the number average molecular weight of the poly(arylene ether nitrile) is 20,000-200,000, for example, 20,000, 40,000, 60,000, 80,000, 100,000, 130,000, 150,000 or 200,000, and the number average molecular weight is measured by gel permeation chromatography based on polystyrene calibration according to GB / T 21863-2008.

[0019] Preferably, the resin is any one of epoxy resin, cyanate ester, polyphenylene ether, maleimide resin, hydrocarbon resin, acrylate resin, polyimide resin, silicone resin, polyester resin or polystyrene, or a combination of at least two thereof.

[0020] Preferably, the epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.

[0021] Preferably, the filler is an inorganic filler.

[0022] Preferably, the filler is a silica filler, preferably spherical silica.

[0023] Preferably, the resin composition further comprises a curing agent, and the curing agent comprises any one of phenolic resin and active ester or a combination of both.

[0024] Preferably, the phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.

[0025] In the present invention, when the main resin contains epoxy resin, its curing agent can be phenolic resin, active ester, etc., while thiol or amine curing agents (such as dicyandiamide or aromatic amine, etc.) should not be used. Such curing agents will cause the CTE of the film to increase and the modulus to decrease after curing.

[0026] Preferably, the content of the curing agent in the resin composition is 10-30 parts by weight, for example, 10 parts by weight, 15 parts by weight, 18 parts by weight, 20 parts by weight, 23 parts by weight, 25 parts by weight, 28 parts by weight or 30 parts by weight.

[0027] In the present invention, a thermoplastic resin may be further added without affecting the comprehensive performance of the resin composition. Examples of the thermoplastic resin include polyvinyl acetal resin, polyamide-imide resin, polyether sulfone resin, polysulfone resin and the like.

[0028] On the other hand, the present invention provides a resin glue solution, which is obtained by dissolving or dispersing the above-mentioned resin composition in a solvent.

[0029] As the solvent in the present invention, there is no particular limitation. As specific examples, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol-methyl ether, carbitol, and butyl carbitol, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethoxyethyl acetate and ethyl acetate, nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be cited. The above solvents can be used alone or in combination of two or more. Preferably, aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene are mixed with ketone fluxes such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The amount of the solvent used can be selected by those skilled in the art according to their own experience so that the obtained resin glue reaches a viscosity suitable for use.

[0030] On the other hand, the present invention provides an adhesive film, which includes a release film, the resin composition as described above attached to the release film after coating and drying, and a protective film covering the resin composition.

[0031] The adhesive film of the present invention, because it contains the resin composition as described above, can have higher toughness, higher copper foil peeling strength and lower CTE.

[0032] Preferably, the thickness of the adhesive film is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.

[0033] Preferably, after curing, the CTE of the adhesive film is less than 50ppm / ℃, for example, 48ppm / ℃, 45ppm / ℃, 40ppm / ℃, 38ppm / ℃, 35ppm / ℃, 30ppm / ℃, 28ppm / ℃, 25ppm / ℃, 20ppm / ℃, 18ppm / ℃, 15ppm / ℃ or 10ppm / ℃, etc.

[0034] Preferably, the modulus of the adhesive film after curing is greater than 4.0 GPa, for example 4.2 GPa, 4.5 GPa, 4.8 GPa, 5.0 GPa, 5.2 GPa, 5.5 GPa, 5.8 GPa, 6.0 GPa, 6.2 GPa, 6.5 GPa, 6.8 GPa or 7.0 GPa.

[0035] Preferably, after the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm, for example, 6.2 N / cm, 6.5 N / cm, 6.8 N / cm, 7.0 N / cm, 7.2 N / cm, 7.5 N / cm, 7.8 N / cm or 8.0 N / cm.

[0036] On the other hand, the present invention provides a resin-coated copper foil, comprising a copper foil, a resin layer and a protective film coated on the resin layer, wherein the resin layer is the above-mentioned resin composition attached to the copper foil after coating and drying.

[0037] Preferably, the thickness of the resin layer is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.

[0038] Preferably, the copper foil has a thickness of 1-105 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm or 105 μm, preferably 3-35 μm, further preferably 5-18 μm.

[0039] In another aspect, the present invention provides a prepreg, comprising a substrate and the above-mentioned resin composition attached to the substrate by impregnation and drying.

[0040] The semi-cured sheet of the present invention may also be referred to as a prepreg or a bonding sheet, and the substrate of the present invention may also be referred to as a reinforcing material.

[0041] Preferably, the substrate is E-glass fiber cloth, NE-glass fiber cloth, quartz glass fiber cloth or aromatic amine cloth.

[0042] In another aspect, the present invention provides a laminate comprising at least one prepreg as described above.

[0043] In another aspect, the present invention provides a metal foil-clad laminate, comprising one or at least two laminated prepregs as described above, and metal foil located on one side or both sides of the laminated prepregs.

[0044] Preferably, the metal foil is copper foil.

[0045] In another aspect, the present invention provides a printed circuit board, comprising one or at least two laminated prepregs as described above.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] In the present invention, the first toughening agent and the second toughening agent are used in combination to exert a synergistic effect, so that the adhesive film and the resin-coated copper foil prepared from the resin composition can better solve the problem of poor toughness caused by the addition of high-filled inorganic fillers, and at the same time have higher Tg, high copper foil peeling strength and low CTE performance, and have excellent comprehensive performance. They can be applied to printed circuit boards of multi-layer laminates, especially printed circuit boards of multi-layer laminates with fine circuits. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] Example 1

[0050] 33 parts of epoxy resin (HEXION, EPR627) and 16 parts of phenolic resin (Dow Chemical, XZ92741), 40 parts of silica (admatechs, 2050MB), 1 part of the first toughening agent (Nipol1072CG, ZEON), and 10 parts of the second toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0051] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0052] Example 2

[0053] 27 parts of epoxy resin (Nippon Kayaku, NC3000H) and 13 parts of active ester (Japan DIC, HPC-8000-65T), 40 parts of silica (admatechs, 2050MB), 5 parts of the first toughening agent (Nipol1072CG, ZEON), and 15 parts of the second toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0054] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0055] Example 3

[0056] 30 parts of epoxy resin (Momentive, EPIKOTE1001) and 15 parts of phenolic resin (Japan Meiwa, 7851H), 40 parts of silica (admatechs, 2050MB), 10 parts of the first toughening agent (AC-3816, Aiko Co., Ltd.), and 5 parts of the second toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0057] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0058] Example 4

[0059] 20 parts of cyanate (Lonza, BA3000) and 25 parts of maleimide resin (CYTEC, M5250), 40 parts of silica (admatechs, 2050MB), 5 parts of a first toughening agent (YP-50S, Nippon Steel Chemical), and 10 parts of a second toughening agent (PENID300, Idemitsu Kosan, Japan) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0060] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0061] Example 5

[0062] 25 parts of polyphenylene ether (SABIC, MX90) and 20 parts of hydrocarbon resin (Japan Soda, B3000), 40 parts of silica (admatechs, 2050MB), 5 parts of the first toughening agent (LP-9013, Mitsubishi Chemical), and 10 parts of the second toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0063] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0064] Example 6

[0065] The difference from Example 1 is that the phenolic resin (Dow Chemical, XZ92741) is replaced by an equal weight portion of dicyandiamide (purchased from BASF).

[0066] Comparative Example 1

[0067] 40 parts of epoxy resin (HEXION, EPR627), 20 parts of phenolic resin (Dow Chemical, XZ92741), and 40 parts of silica (admatechs, 2050MB) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0068] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0069] Comparative Example 2

[0070] 30 parts of epoxy resin (Momentive, EPIKOTE1001) and 15 parts of phenolic resin (Japan Meiwa, 7851H), 40 parts of silica (admatechs, 2050MB), and 15 parts of core-shell rubber (AC-3816, Aiko Corporation) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0071] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0072] Comparative Example 3

[0073] 30 parts of epoxy resin (Momentive, EPIKOTE1001) and 15 parts of phenolic resin (Japan Meiwa, 7851H), 40 parts of silica (admatechs, 2050MB), and 15 parts of polyarylether nitrile toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0074] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0075] Comparative Example 4

[0076] 27 parts of epoxy resin (Nippon Kayaku, NC3000H) and 13 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 20 parts of nitrile rubber (ZEON, Nipol 1072CG) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0077] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0078] Comparative Example 5

[0079] 27 parts of epoxy resin (Nippon Kayaku, NC3000H) and 13 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 20 parts of polyarylethernitrile toughening agent (PEN-1100, Sichuan Chemical New Materials) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0080] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0081] Comparative Example 6

[0082] The difference from Example 1 is that the second toughening agent (PEN-1100, Sichuan Chemical New Materials) is replaced by an equal weight portion of modified polyether ketone (Evonik, 1000P).

[0083] Comparative Example 7

[0084] The difference from Example 1 is that the second toughening agent (PEN-1100, Sichuan Chemical New Materials) is replaced by an equal weight portion of polyethersulfone (SOLVAY, 3600RP).

[0085] The performance test comparison of the above embodiments and comparative examples is shown in Table 1 below:

[0086] (1) Bending resistance: Tested according to the method specified in JIS C-6471, test conditions 0.5kg / 0.8R;

[0087] (2) Copper foil peel strength: The peel strength of the copper foil layer of the surface copper electroplating is tested using the IPC-TM-650 2.4.9 method;

[0088] (3) Fine line reliability: the percentage of short circuits in the test circuit after reflow soldering. When the percentage is greater than 90%, it is "excellent", when the percentage is less than 80%, it is "poor", and the rest is "good";

[0089] (4) CTE: measured according to the TMA test method specified in IPC-TM-650 2.4.24.5.

[0090] (5) Tg (DSC): tested using IPC-TM-650 2.4.25 method;

[0091] (6) DMA modulus: measured according to the DMA test method specified in IPC-TM-650 2.4.24.4.

[0092] Table 1

[0093]

[0094]

[0095] Table 2

[0096]

[0097] As can be seen from Table 1, the films of Examples 1-5 have good toughness (bending resistance greater than 1000 times), high copper foil peeling strength, excellent comprehensive performance of Tg, modulus and CTE, and excellent reliability of thin circuits. Example 6 uses dicyandiamide curing agent to cure epoxy, so that the film has a large CTE and low modulus.

[0098] Comparative Example 1 did not add the toughening agent described in the present invention, and the film toughness was poor (bending resistance was only 50 times), and the copper foil peeling strength was low; Comparative Examples 2 and 4 only added the first toughening agent (core-shell rubber or nitrile rubber), the film CTE increased, Tg decreased, modulus decreased, copper foil peeling strength was also low, and the overall performance deteriorated; Comparative Examples 3 and 5 only added the second toughening agent polyarylethernitrile, and the film toughness performance was obviously not as good as the case of using a toughening agent in combination in the embodiment. Comparative Examples 6 and 7 replaced the second toughening agent polyarylethernitrile with other toughening agents, the film toughness was poor, the copper foil peeling strength was low, and the properties such as Tg and modulus were also reduced, and the overall performance was not good.

[0099] The applicant declares that the present invention uses the above embodiments to illustrate the resin composition of the present invention and the adhesive film and printed circuit board containing the same, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that The resin composition comprises the following components in parts by weight: The resin is any one of epoxy resin, cyanate ester, polyphenylene ether, maleimide resin or hydrocarbon resin, or a combination of at least two thereof; The first toughening agent includes any one of nitrile rubber, acrylic rubber, core-shell rubber or phenolic resin or a combination of at least two thereof; The second toughening agent is poly(arylene ether nitrile).

2. The resin composition according to claim 1, characterized in that The epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.

3. The resin composition according to claim 1, characterized in that The filler is an inorganic filler.

4. The resin composition according to claim 3, characterized in that The filler is a silicon dioxide filler.

5. The resin composition according to claim 4, characterized in that The filler is spherical silica.

6. The resin composition according to claim 1, characterized in that The resin composition further comprises a curing agent, and the curing agent comprises any one of phenolic resin and active ester or a combination of both.

7. The resin composition according to claim 6, characterized in that The phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.

8. The resin composition according to claim 6, characterized in that The content of the curing agent in the resin composition is 10-30 parts by weight.

9. A resin glue, characterized in that: The resin composition is obtained by dissolving or dispersing the resin composition as claimed in any one of claims 1 to 8 in a solvent.

10. An adhesive film, characterized in that: The adhesive film comprises a release film, a resin composition according to any one of claims 1 to 8 attached to the release film after coating and drying, and a protective film covering the resin composition.

11. The adhesive film according to claim 10, characterized in that: The thickness of the adhesive film is 5-300 μm.

12. The adhesive film according to claim 11, characterized in that: The thickness of the adhesive film is 10-200 μm.

13. The adhesive film according to claim 12, characterized in that: The thickness of the adhesive film is 20-100 μm.

14. The adhesive film according to claim 10, characterized in that: After the adhesive film is cured, the CTE is less than 50 ppm / °C.

15. The adhesive film according to claim 10, characterized in that: The modulus of the adhesive film after curing is greater than 4.0 GPa.

16. The adhesive film according to claim 10, characterized in that: After the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm.

17. A resin-coated copper foil, characterized in that: The resin-coated copper foil comprises a copper foil, a resin layer and a protective film coated on the resin layer. The resin layer is a resin composition as claimed in any one of claims 1 to 8 attached to the copper foil after coating and drying.

18. The resin-coated copper foil according to claim 17, characterized in that The thickness of the resin layer is 5-300 μm.

19. The resin-coated copper foil according to claim 18, characterized in that The thickness of the resin layer is 10-200 μm.

20. The resin-coated copper foil according to claim 19, characterized in that The thickness of the resin layer is 20-100 μm.

21. The resin-coated copper foil according to claim 20, characterized in that The copper foil has a thickness of 1-105 μm.

22. A prepreg, characterized in that: The prepreg comprises a substrate and the resin composition according to any one of claims 1 to 8 attached to the substrate after impregnation and drying.

23. A laminated board, characterized in that: The laminate comprises at least one prepreg according to claim 22.

24. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises one or at least two stacked prepregs as claimed in claim 22, and metal foil located on one side or both sides of the stacked prepregs.

25. A printed circuit board, characterized in that: The printed circuit board comprises one or at least two superimposed prepregs according to claim 22.

Citation Information

Patent Citations

  • Preparation method of epoxy adhesive film with long room-temperature storage period

    CN114806447A